You Ci Ke - Han, Qingping (2015)
You Ci Ke is an animation about a mysterious animal that wins its way into the heart of an emperor, much to the dismay of his loyal servant Nucai. Amidst Nucai’s struggle to regain the emperor’s favour, he discovers something sinister about the emperor’s new pet.